A SCIENTIFIC APPROACH TO HERBAL ANTI-DANDRUFF SERUM DEVELOPMENT AND EVALUATION - Verma, Anuj Kumar; Reetu, Reetu; Yadav, Ashutosh Kumar (International Journal of Pharma and Bio Sciences, 2026)
Dandruff is a prevalent scalp condition characterized by white or yellowish flakes of dead skin, frequently accompanied by itching and irritation. It is primarily caused by overgrowth of the opportunistic fungus Malassezia furfur, which, while not a serious medical condition, can substantially impair self-confidence and, in chronic cases, may contribute to alopecia. This study describes the formulation and evaluation of a polyherbal anti-dandruff hair serum comprising Abutilon indicum leaf extract, neem (Azadirachta indica) bark extract, eucalyptus (Eucalyptus globulus) essential oil, menthol, and Aloe barbadensis (aloe vera) gel. Each ingredient was selected for its well-documented antifungal, antibacterial, and scalp-conditioning properties. The serum was evaluated for organoleptic and physicochemical parameters including color, fragrance, pH, density, viscosity, skin irritation (patch test), and anti-dandruff efficacy (agar well diffusion method). The formulation displayed a uniform yellowish-green appearance, a pH of 6.0 (within the optimal scalp-compatible range of 4.5–6.5), a density of 1.027 g/mL, and a viscosity of 1.1 cP. Skin patch testing on 10 volunteers demonstrated no irritation, and microbiological assessment confirmed significant antifungal activity against Malassezia furfur. The serum exhibited excellent stability, nourishing properties, and anti-dandruff efficacy, indicating strong potential as a safe and effective natural alternative to synthetic anti-dandruff formulations.